Characteristics of Impingement Diesel SPray Adhesion on a Flat Wall - Akop, M.Z.; Arifin, Y.M.; Salim, M.A.; Mansor, M.R.; Mohd Rosli, M.A.; Tahir, M.M.; Saad, A.M. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
Many researchers since last decade have been looking forward to improving diesel engine performance through keeping low harmful emission. The aim of this study was to clarify the fundamental characteristics of nonevaporated impinging spray and adhesion behavior of fuel by measuring the adhering fuel mass on a wall. In this study, a fuel injection system, a high pressure vessel and an image processing unit for impingement spray were used. Experimental investigations were carried out with various injection pressures from 40 MPa to 170 MPa and ambient pressures from 0.1 MPa to 4.0 MPa. The impingement distances were set from 30 mm to 90 mm. The results showed the adhered fuel mass was affected by impingement distances. The adhered mass ratio was inversely proportional to injection pressure. At higher ambient pressure and higher the injection pressure, adhered mass fuel tended to decrease. Adhered fuel mass ratio had the potential to decline after reaching its peak when impingement velocity decreased beyond a critical velocity.